Democracy and corruption: a complex relationship - Saha, Shrabani (Crime, law and social change, 2014)
We argue that an ‘electoral democracy’ is not sufficient to reduce corruption. Our contention is that the institutions associated with mature democracy are crucial to successfully deterring corrupt behaviour. At the core of our argument is the idea that with well-functioning institutions, the probability of detection and punishment is sufficiently high to deter most decision makers from choosing to act corruptly. The empirical evidence we present supports this idea. The nonlinearity of democracy variables is tested to confirm that an advanced stage of democracy is crucial for combating corruption.